Probing corrosion initiation at interfacial nanostructures of AA2024-T3. (15th February 2017) - Parvizi, Reza; Hughes, Anthony E.; Tan, Mike Y.; Marceau, Ross K.W.; Forsyth, Maria; Cizek, Pavel; Glenn, Alexander M.
Graphical abstract: Highlights: Early stages of corrosion of AA2024-T3 were investigated at near-atomic scales. Compositions of the corroded nanostructures were quantified by atom probe. High-density near-surface defect structures were found to trigger corrosion. Dislocation arrays were discovered as pathways for corrosive species. Abstract: High-strength aluminium alloys such as AA2024-T3 are often developed by the introduction of plastic deformation to a precipitate containing microstructure. These alloys contain complex, near-surface nanostructures whose effects on localised corrosion processes have not been well understood due primarily to the difficulty of characterising these heterogeneous compositions and structures. In this work, we observed entangled oxide networks co-located with dislocation structures piled up at corroded intermetallic particles of an AA2024-T3 alloy. It was revealed that dislocation arrays act as pathways for corrosive species and promote structural degradation at interfacial regions, providing a new insight into corrosion initiation at the nano-scale.